Pemetaan Artikel Jurnal Go Green di Universitas Diponegoro: Analisis Bibliometrik dengan Visualisasi VOSviewer - Esa Fitri Amalia; Putut Suharso (Jurnal Pustaka Ilmiah)
This study aims to determine the mapping of Go Green Diponegoro University journal articles in the Scopus database from 2013-2022 with bibliometric analysis. The method used is quantitative descriptive bibliometrics with VOSviewer analysis of co-authorship, co-occurrences, citation and data retrieval through Scopus journals. The results of the research for ten years produced 152 total documents, the growth of documents in each year is still fluctuating, but there has begin to be a steady increase starting from 2019-2022, the most productive researcher is Kusworo T.D with 9 documents and the researcher with the most citations is Sasmono R. T with 166 citations, the publishing institution that publishes the most Go Green articles is Heliyon, the institution that collaborates the most with Diponegoro University is the Ministry of Research Technology and Higher Education of the Republic of Indonesia, the collaborating countries are Japan and Malaysia, the most keywords from the author's point of view are 'antioxidant' (4) and 'growth' (4) and seen from the index keywords the most are 'controlled study' (24) and 'male' (23), while for keywords that are still low in frequency are climate change, energy optimization, water, waste and zinc, and the average citation per document is obtained 11.47%. The article with the most citations is the article Zhou b., et.al with 543 citations and the article with the most links is the article Fahri s., et.al with 3 links, while the journal that has the most citations is occupied by The Lancet journal with 543 citations.